Contemporary Results of Aortic Coarctation Repair Through Left Thoracotomy - Mery, Carlos M.; Guzmán-Pruneda, Francisco A.; Trost, Jeffrey G.; McLaughlin, Ericka; Smith, Brendan M.; Parekh, Dhaval R.; Adachi, Iki; Heinle, Jeffrey S.; McKenzie, E. Dean; Fraser, Charles D. (The Annals of thoracic surgery, 2015)
Although surgical results for repair of coarctation of the aorta (CoA) have steadily improved, management of this condition remains controversial. The purposes of this study were to analyze the long-term outcomes of patients undergoing CoA repair through left thoracotomy and to define risk factors for reintervention. All patients who were less than 18 years old and who underwent initial repair of CoA through left thoracotomy from 1995 to 2013 at Texas Children’s Hospital (Houston, TX) were included. Patients were classified into 3 groups: 143 (42%) neonates (0 to 30 days old), 122 (36%) infants (31 days to 1 year old), and 78 (23%) older children (1 to 18 years old). Univariate and multivariate analyses were performed. A total of 343 patients (129 [38%] girls) with median age of 53 days (interquartile range [IQR],12 days to 9 months) and weight of 4.1 kg (IQR, 3.1 to 8.0) underwent repair with extended end-to-end anastomosis (291 patients [85%]), end-to-end anastomosis (44 patients [13%]), interposition graft (2 patients [0.6%]), or subclavian flap (6 patients [2%]). Concomitant diagnoses included genetic abnormalities (48 patients [14%]), isolated ventricular septal defects (58 patients [17%]), small left-sided structures (53 patients,16%), or other complex congenital heart disease (18 patients [5%]). Perioperative mortality was 1% (n = 4, all neonates). At a median follow-up of 6 years (7 days to 19 years), only 14 (4%) patients required reintervention (10 catheter-based procedures, 6 surgical repairs). A postoperative peak velocity of 2.5 m/s or greater was an independent risk factor for reintervention (odds ratio [OR], 4.0; 95% confidence interval [CI], 1.4 to 11.6). Within the cohort, 95 (33%) patients were hypertensive or remained on cardiac medications a median of 12 years (6 months to 19 years) after the surgical procedure. Development of perioperative hypertension was associated with higher risk of chronic hypertension or cardiac medication dependency (OR, 1.9; 95% CI, 1.1 to 3.3). CoA repair through left thoracotomy is associated with low rates of morbidity, mortality, and reintervention. Aortic arch obstruction should be completely relieved at the time of surgical intervention to minimize the risk of long-term recoarctation.